Iron‐Catalysed Selective Aerobic Oxidation of Alcohols to Carbonyl and Carboxylic Compounds. Issue 11 (28th July 2016) - Lagerblom, Kalle; Wrigstedt, Pauli; Keskiväli, Juha; Parviainen, Arno; Repo, Timo
Abstract: A method for aerobic alcohol oxidation catalysed by Fe(NO3 )3 /2, 2'‐bipyridine/TEMPO has allowed highly selective conversion of primary alcohols into either aldehydes or carboxylic acids in one‐step. The oxidation of primary alcohols proceeded selectively to aldehydes, as TEMPO was present in the reaction. Nevertheless, the aldehydes were further oxidized into carboxylic acids as the reaction time was extended. Detailed investigation of the reaction suggested, that the deoxygenation of TEMPO into TMP enabled the auto‐oxidation of aldehydes to carboxylic acids, which was initially inhibited in the presence of TEMPO. The procedure was also efficient in oxidation of secondary alcohols when TEMPO was replaced by the less sterically hindered ABNO. Abstract : A highly selective aerobic oxidation of primary alcohols into either aldehydes or carboxylic acids has been developed. This mild and practical method used Fe(NO3 )3 /TEMPO/2, 2'‐bipyridine as a catalyst in aerobic conversion of alcohols into aldehydes (see figure). Further oxidation into carboxylic acids was achieved in extended reactions where TEMPO was de‐oxygenated into TMP. The procedure was also efficient for the oxidation of secondary alcohols when TEMPO was replaced by the less sterically hindered ABNO.